1999
DOI: 10.1046/j.1365-2958.1999.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

CtsR, a novel regulator of stress and heat shock response, controls clp and molecular chaperone gene expression in Gram‐positive bacteria

Abstract: SummaryclpP and clpC of Bacillus subtilis encode subunits of the Clp ATP-dependent protease and are required for stress survival, including growth at high temperature. They play essential roles in stationary phase adaptive responses such as the competence and sporulation developmental pathways, and belong to the so-called class III group of heat shock genes, whose mode of regulation is unknown and whose expression is induced by heat shock or general stress conditions. The product of ctsR, the first gene of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
367
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(394 citation statements)
references
References 78 publications
22
367
1
4
Order By: Relevance
“…Several classes of stress-response genes have been described in L. monocytogenes, which are activated during exposure to specific or general stresses. In particular, the class I and class III heat-shock and the SigB response have been investigated thoroughly (Derre et al, 1999;Hanawa et al, 1999;Kazmierczak et al, 2003). Recently, it has been shown that the SOS response of L. monocytogenes is activated upon mild heat exposure (van der Veen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several classes of stress-response genes have been described in L. monocytogenes, which are activated during exposure to specific or general stresses. In particular, the class I and class III heat-shock and the SigB response have been investigated thoroughly (Derre et al, 1999;Hanawa et al, 1999;Kazmierczak et al, 2003). Recently, it has been shown that the SOS response of L. monocytogenes is activated upon mild heat exposure (van der Veen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Class II Hsps are s B dependent, and are induced by heat and other stresses (Schulz & Schumann, 1996). Class III Hsps are Clp proteases/ ATPases, and are typically under the control of the transcriptional repressor CtsR (Derre et al, 1999). The class IV Hsps are encoded by genes that are not controlled by HrcA, s B or CtsR (Helmann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For 20 of the 37 genes, additional regulation by secondary regulators has already been proven by previous studies. These 20 genes are: bioB, bmrR, purK, radA, yacK, yacM, ydaF, ykrT, yocL, ypuD, yraA, ysnF, ywhH, yxjG and the operon yceC-yceD-yceE-yceF-yceG-yceH (Au et al, 2005;Banse et al, 2008;Baranova et al, 1999;Bower et al, 1996; Cao et al, 2002;Chu et al, 2006;Chumsakul et al, 2011;Comella & Grossman, 2005;Derré et al, 1999;Drzewiecki et al, 1998;Ebbole & Zalkin, 1987;Eiamphungporn & Helmann, 2008;Erwin et al, 2005;Grundy & Henkin, 1998; Höper et al, 2005;Jervis et al, 2007;Kearns et al, 2005; Krüger et al, 1996;Kumaraswami et al, 2010;Leelakriangsak et al, 2007;Lei et al, 2009;Marvasi et al, 2010;Nakano et al, 2003;Nguyen et al, 2009;Perkins et al, 1996; Petersohn et al, 2001;Sekowska & Danchin, 2002;Wang et al, 2006;Weng et al, 1995; You et al, 2008). Details about their secondary regulators are included in Supplementary Table S4.…”
mentioning
confidence: 99%